Impact of Travel Distance and Urban‐Rural Status on the Multidisciplinary Management of Rectal Cancer. Issue 4 (7th October 2016) - Loree, Jonathan M.; Javaheri, Khodadad R.; Lefresne, Shilo V.; Speers, Caroline H.; Ruan, Jenny Y.; Chang, Jennifer T.; Brown, Carl J.; Kennecke, Hagen F.; Olson, Robert A.; Cheung, Winson Y.
Abstract: Objectives: Optimal treatment of rectal cancer (RC) requires multidisciplinary care. We examined whether distance to treatment center or community size impacts access to multimodality care and population‐based outcomes in RC. Methods: Patients diagnosed with stage II/III RC from 1999 to 2009 and treated at 1 of 6 regional cancer centers in British Columbia were reviewed. Distance to treatment center was determined for each patient. Communities were classified as rural, small, medium, and large population centers. Logistic and Cox regression models assessed associations of distance and community size with treatment received as well as cancer‐specific (CSS) and overall survival (OS). Results: Of 3, 158 patients, 93.6% underwent surgery, 86.3% received radiotherapy, and 51.3% were treated with adjuvant chemotherapy (AC). Median time from diagnosis to oncologic consultation was longer for those >100 km from a treatment center or residing in medium/rural communities. Logistic regression demonstrated no correlation between distance or community size and receipt of treatment modality. Univariate analysis showed similar CSS ( P = .18, .88) and OS ( P = .36, .47) based on community size and distance, respectively. In multivariate analysis, distance >100 km had inferior CSS (Hazard Ratio [HR] 1.39, 95% CI: 1.03‐1.88; P = .031). There was no consistent trend between decreasing community size and outcomes; however, living in a small center was associated with improved OS (HR 0.58, 95% CI: 0.38‐0.88; P = .011) and CSS (HR 0.42, 95% CI: 0.25‐0.70; P = .001). Conclusions: In this population‐based study, there were no urban‐rural differences in access to multidisciplinary care, but increased distance may be associated with worse cancer‐specific outcomes.